ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KECAMATAN DETUKELI - Ringgi, Yovita; Londa, Yulitа; Kapa, Sesilianus (Program Studi Akuntansi Universitas Flores, 2025)
The purpose of this study was to determine the effect of taxpayer awareness, tax sanctions, and taxpayer income on taxpayer compliance in paying land and building taxes. This type of research is causality. The population in this study is land and building tax payers in the Detukeli sub-district until 2022, totaling 3,442. The sampling technique used purposive sampling. The number of samples in this study were 98 taxpayers. This study uses primary data, namely a questionnaire. Data were analyzed using multiple regression analysis which was processed using IMB SPSS Statistics ver 29. The results of the study show that: (1) taxpayer awareness influences compliance with paying land and building taxes. The test results show that the coefficient value of the taxpayer awareness variable is 0.426 with t count > t table (5.228 > 1.66123) and a significant level of 0.001 < 0.05. (2) tax sanctions have no effect on compliance with paying land and building taxes. The test results show that the coefficient value of the tax penalty variable is -0.119 with t count < t table -0.797 <1.66123) and a significant level of 0.427 > 0.05. (3) taxpayer income affects compliance with paying land and building taxes. The test results show that the coefficient value of the taxpayer income variable is 0.353 with t count > t table (2.168> 1.66123) and a significant level of 0.033 <0.05. Simultaneously, the variables of taxpayer awareness, tax sanctions, and taxpayer income have a significant effect on compliance with paying land and building taxes by 22,5%. While the remaining 77,5% is influenced by other variables not included in the study.